2018
DOI: 10.1186/s12958-018-0431-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiations and male fertility

Abstract: During recent years, an increasing percentage of male infertility has to be attributed to an array of environmental, health and lifestyle factors. Male infertility is likely to be affected by the intense exposure to heat and extreme exposure to pesticides, radiations, radioactivity and other hazardous substances. We are surrounded by several types of ionizing and non-ionizing radiations and both have recognized causative effects on spermatogenesis. Since it is impossible to cover all types of radiation sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
114
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(126 citation statements)
references
References 151 publications
(208 reference statements)
3
114
0
9
Order By: Relevance
“…Thus, it has been suggested that testicles are more sensitive to RFR. Kesari et al [34] reported that RF-EMF might cause oxidative stress with an increased level of reactive oxygen species, which may provoke infertility. Another study reported that electromagnetic radiation emitted from Wi-Fi (2450 MHz) and cellular phones (900 and 1800 MHz) causes an increase in lipid peroxidation and a decrease in the levels of antioxidant trace elements (copper and zinc) along with TAS and glutathione (GSH) in the kidneys and testicles of rats in their development periods, and thus leads to oxidative stress [29].…”
Section: Analysis Of Tas Tos Osi 8-ohdg and Mdamentioning
confidence: 99%
“…Thus, it has been suggested that testicles are more sensitive to RFR. Kesari et al [34] reported that RF-EMF might cause oxidative stress with an increased level of reactive oxygen species, which may provoke infertility. Another study reported that electromagnetic radiation emitted from Wi-Fi (2450 MHz) and cellular phones (900 and 1800 MHz) causes an increase in lipid peroxidation and a decrease in the levels of antioxidant trace elements (copper and zinc) along with TAS and glutathione (GSH) in the kidneys and testicles of rats in their development periods, and thus leads to oxidative stress [29].…”
Section: Analysis Of Tas Tos Osi 8-ohdg and Mdamentioning
confidence: 99%
“…Human fertility has declined markedly due to various factors, such as ecological environmental pollution, an increase in work-related stress, unhealthy living habits, and sexually transmitted diseases [1][2][3][4]. The prevalence of infertility ranges from 10 to 15% among couples.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors, such as urogenital infections, endocrine disorders, immunological factors and drug-related damage, affect the male reproductive system and lead to infertility [1,2]. The specific mechanisms underlying the effects of these factors on male infertility may include spermatogenesis, hormone regulation, oxidative stress, and the regulation of spermatogenesis-related genes [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of EMFs on human tissues depends on the value of the specific absorption rate (SAR) which relies on the duration of exposure to radiation, its intensity, polarization and frequency [32,33]. A higher SAR may be associated with keeping the device in a trouser pocket, using a laptop connected to Wi-Fi, and keeping the phone close to the head while talking.…”
Section: Introductionmentioning
confidence: 99%
“…Semen quality, which is considered one of the key factors influencing reproductive success, may decrease after exposure to various common sources of EMF (laptop computers, mobile phones, and many wireless Internet-connected devices) [24,35,36]. It is suggested that sperm parameters such as motility, morphology, viability, sperm count and concentration, can be adversely affected and decreased by the use of mobile phones [32,33,35,37,38]. Several studies suggest that the rapid progressive motility of spermatozoa may be decreased by carrying mobile phones in the trouser pocket [39,40].…”
Section: Introductionmentioning
confidence: 99%